A systematic mapping study on IoT-based software systems for precision agriculture. (5th May 2023) - Lopes, Vinícius C.; Silva, Cleiton; Gonçalves, Dayana; Oliveira, Roberto; Bulcão-Neto, Renato; Kassab, Mohamad; Graciano-Neto, Valdemar V.
Agriculture is often pressured to adopt new technologies so that production rate can be accordingly increased. The Internet of Things (IoT) has played an essential role in modernising the agricultural practices once it can support monitoring and automated decisions on planting. Given the ascending adoption of IoT in agriculture, the main goal of this study is reporting collected evidence from the literature and summarise how IoT systems have been used to support several activities in the agriculture domain. We adopted the Systematic Mapping Study (SMS) procedure. We designed a search string executed in two Web search engines: Scopus and Embrapa repositories. We selected a total of 35 primary studies that either propose or evaluate IoT-based systems in the agriculture domain. Results suggest that, although there are different platform solutions such as web-based systems, web-and-mobile-based systems and mobile systems targeting activities such as planting monitoring and irrigation, there are still several opportunities in the area, such as (i) the conception of automated decision-making processes and supporting technologies for agriculture recurrent activities, (ii) adoption of edge computing and machine learning for information processing and automation, respectively and (iii) proposition of solutions towards reducing production costs and ecological impacts.